A novel strategy towards sustainable and stable nitritation-denitritation in an A-B process for mainstream municipal wastewater treatment - Gu, Jun (2020)
The conventional activated sludge process is increasingly receiving concerns for its high energy consumption and excess sludge production. To cope with these issues, an A-B process for nitrogen removal via nitritation-denitritation was proposed in previous study which showed the possibility to achieve energy self-sufficient wastewater reclamation. However, nitritation-denitritation in such a process could not be sustained due to excessive COD capture at A-stage. In this study a novel A-B process configuration in which a portion of influent was directed to B-stage was developed for sustainable and stable nitrogen removal via nitrite shunt with minimal impacts on energy recovery. In this process configuration, the bypass flow was found to significantly shape microbial community structure by enriching ammonia oxidizer and denitrifiers against nitrite oxidizer. As the result, about 78% of total nitrogen was removed via nitritation-denitritation. In addition, the potential energy recovery and sludge reduction were not compromised in the proposed A-B process with the bypass of influent to B-stage. It is expected that this study may offer a feasible engineering solution for concurrently achieving direct energy recovery from wastewater at A-stage, and sustainable nitritation-denitritation for nitrogen removal at B-stage.